Why We Need a World Development Organisation - Taylor, Ian (Malaysian Journal of International Relations, 2015)
Since the early 1980s, a philosophical approach to economics and development, one that is broadly in alignment with the neoliberal mantra of liberalisation, privatisation and the "free market" has become hegemonic. Despite the evident intellectual bankruptcy of relying on "the market" for development and even after the post-2008 crisis, which exposed neoliberalism’s failures, we have not witnessed any fundamental changes in most international institutions approaches to the most pressing issue of our time: sustainable development. This article seeks to demonstrate that a new organisation specifically aimed at promoting global development and free of the reformist discourses that pervade existing bodies (such as UNCTAD) is needed. Otherwise, debates will continue to be restricted to problem-solving issues, nothing will fundamentally change and global inequality (itself brought about by imperialism and neo-colonialism) will continue to characterise the global political economy.